2020
DOI: 10.1177/2048872620923647
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of acute aortic dissection in patients with out-of-hospital cardiopulmonary arrest evaluated by non-contrast computed tomography

Abstract: Background The exact epidemiology of acute aortic dissection, including cases of out-of-hospital cardiopulmonary arrest, is unclear. We aimed to investigate the incidence and characteristics of acute aortic dissection in patients with out-of-hospital cardiopulmonary arrest transferred to our institution and validate the related factors to out-of-hospital cardiopulmonary arrest in Stanford type A acute aortic dissection. Methods We retrospectively reviewed the acute-phase computed tomography data of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Up to this point, there are few studies on AAD patients presenting as OHCA, with its epidemiology and patient characteristics remaining mostly unknown [2] . Recent studies have suggested that its incidence is higher than previously reported [3] , [4] ..…”
Section: Introductionmentioning
confidence: 71%
“…Up to this point, there are few studies on AAD patients presenting as OHCA, with its epidemiology and patient characteristics remaining mostly unknown [2] . Recent studies have suggested that its incidence is higher than previously reported [3] , [4] ..…”
Section: Introductionmentioning
confidence: 71%
“…MMP.1, MMP.2, and MMP.9 have been con rmed in a number of experiments to be related to the occurrence of aortic dissection/aneurysm [4][5]. Therefore, AngII may promote the occurrence of aortic dissection [6], and studies have shown that the RAS system plays a role in the occurrence of abdominal aortic aneurysm [7]. Although experiments found that ACE activity in cardiovascular diseases such as heart failure, hypertension, and angina pectoris was signi cantly increased in the disease group [8-10], the detection of peripheral venous blood ACE concentration in this experiment showed contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…The majority had type A pathology versus type B (66 vs. 5) with mechanisms for arrest including pericardial effusion and massive haemorrhage. 2 These findings suggest that acute aortic syndromes play a relevant role in cardiac arrest and underscore the need for greater diagnostic awareness as well as improved prevention.…”
Section: Epidemiologymentioning
confidence: 92%
“…However, the broad availability of high quality axial imaging with computed tomography (CT) has led to greater recognition of acute aortic syndromes as a cause of OHCA. Takeuchi et al 2 describe the findings in a single centre series of 1011 patients with OHCA with 934 undergoing CT and found that 7.6% had an acute aortic syndrome, a frequency that is strikingly high. The majority had type A pathology versus type B (66 vs. 5) with mechanisms for arrest including pericardial effusion and massive haemorrhage.…”
Section: Epidemiologymentioning
confidence: 99%